THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE AND GROWTH COMPANY ON COMPANY VALUE WITH CORPORATE GOVERNANCE AS MODERATING IN MANUFACTURING COMPANIES - Arifin Djakasaputra; Juliana Juliana; Fachrurazi Fachrurazi (SEAN Institute, 2023)
This study aims to determine the effect of Environmental Performance and Company Growth to Mark Company with corporate Governance as moderator on company manufacturers listed on the Indonesia Stock Exchange for the 2016-2019 period. Sampling method using purposive sampling and obtained 60 manufacturing companies listed on the Stock Exchange Indonesia and registered in PROPER period 2016-2019 as sample. Tool analysis data which The method used is Structural Equation Modeling (SEM) using the PLS (Partial Least Square). Results this research shows that Environmental Performance and Company Growth has a significant effect on company value, Good Corporate Governance is able to strengthen connection Among Performance Environment and Growth Company to mark company. Limitations study this is study this only look on sector manufacture and only look at a certain period. And for further research can use other sectors such as services and period observation which more new so that give results which more interesting again.